Using Strategy Maps to assess CRM implementation: a case study of an international IT company in Taiwan - Hsu, Han-Chang (2007)
Today, in order to sustain their competitive advantages and long-term shareholder value, firms have gradually realized the importance of customer relationships, and intend to establish the long-term profitable relationships with their targeted customers to reduce acquisition costs and expand the revenue opportunities by using the CRM solutions. Indeed, CRM solutions do not only enable the firms to easily acquire, warehouse, and analyze customer's data and behavior to develop its customer knowledge, but also effectively manage and enhance the customer relationships through premium customer value propositions, such as premium services and customized communications, to improve customers satisfaction and loyalty (Payne and Frow, 2005; Laudon and Traver, 2004).